A preliminery study on length-weight relationship of the mudskipper Boleophthalmus boddarti in Soc Trang - Quang, Dinh Minh (Academia Journal of Biology, 2014)
Boleophthalmus boddarti (Pallas, 1770) is one of mudskippers (Gobiidae), and a potential commercial fish in Mekong Delta, Vietnam. The study on the goby B. boddarti was investigated in Tran De district, Soc Trang province, Mekong Delta, Vietnam, to establish some basic population biology parameters. A total of 117 individuals were caught in mudflats of Tran De beach by deep net to determine length-weight relationships of this species. After determining sex by external features, total length (TL in cm), and body weight (W in g) of this goby were measured. This study ran for six months, from January 2013 to June 2013. The mean lengths of female significantly differed from value of male, whereas the average body weights of male and female were quite similar. The proportion of male and female groups were not substantially different. The length-weight relationships of total fish, male and female were highly correlated with high regression values which were 0.813, 0.866 and 0.767, respectively. The slope values of this mudskipper was 3.21±0.32 which was not significant higher cubic value (three), suggesting the growth relationship of this species was isometric growth and could be a potential fish for future aquaculture.